2022
DOI: 10.1037/xge0001118
|View full text |Cite
|
Sign up to set email alerts
|

Hello, stranger? Pleasant conversations are preceded by concerns about starting one.

Abstract: Connecting with others makes people happier, but strangers in close proximity often ignore each other. Prior research (Epley & Schroeder, 2014) suggested this social disconnection stems from people misunderstanding how pleasant it would be to talk with strangers. Extending these prior results, in a field experiment with London-area train commuters, those assigned to talk with a stranger reported having a significantly more positive experience, and learning significantly more, than those assigned to a solitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 25 publications
0
42
1
Order By: Relevance
“…In fact, we think people might be even more likely to underestimate the positive outcomes of deep conversations in naturalistic settings outside the lab. Previous research in both the United States and in the United Kingdom indicates that people may underestimate strangers’ willingness to engage in conversation in naturalistic field experiments on trains, busses, and cabs, which can partly then explain people’s tendency to underestimate how much they would enjoy having a conversation with a stranger (Epley & Schroeder, 2014; Schroeder et al, in press; see also Sandstrom & Boothby, 2021). Our experimental procedures eliminate this concern by instructing participants to speak with another study participant who they know will engage them in conversation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, we think people might be even more likely to underestimate the positive outcomes of deep conversations in naturalistic settings outside the lab. Previous research in both the United States and in the United Kingdom indicates that people may underestimate strangers’ willingness to engage in conversation in naturalistic field experiments on trains, busses, and cabs, which can partly then explain people’s tendency to underestimate how much they would enjoy having a conversation with a stranger (Epley & Schroeder, 2014; Schroeder et al, in press; see also Sandstrom & Boothby, 2021). Our experimental procedures eliminate this concern by instructing participants to speak with another study participant who they know will engage them in conversation.…”
Section: Discussionmentioning
confidence: 99%
“…The generalizability of our effects could also be tested using diary methods in which people are asked to engage in relatively deeper or shallower conversations over the course of a day and then report their experiences at the end of the day, or simply by asking people to engage in a deeper conversation when they have a natural opportunity to do so in daily life. Existing research using this methodology has found that people report more positive affect when asked to act extraverted than when asked to act introverted (Margolis & Lyubomirsky, 2020), when asked to engage in conversation on a train or bus compared with remaining silent (Epley & Schroeder, 2014; Schroeder et al, in press), or simply when asked to try to make a connection to a coffee shop barista compared with being as efficient as possible (Sandstrom & Dunn, 2014a; see also Gunaydin et al, 2021). These existing results, showing positive affect resulting from simply engaging with others in naturalistic settings, give us reason to believe that engaging more deeply in these same settings would enhance positive affect as well.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our experiments advance research on people’s predictions about conversation. Prior research typically measures people’s predictions in a single measure of their expected enjoyment or liking for their conversation partner (Epley & Schroeder, 2014; Mallett et al, 2008; Schroeder et al, 2021; Zelenski et al, 2013). Our experiments add nuance to this research by measuring the predicted trajectory of enjoyment during conversation, revealing that people misunderstand the progression of their enjoyment over time.…”
Section: Discussionmentioning
confidence: 99%
“…Every interaction entails a series of decision points, including engaging others in conversation, managing an ongoing conversation, and disengaging from the conversation. Previous research has primarily examined psychological processes that can lead to errors at the first two decision points: For example, people tend to be reluctant to initially engage with strangers (Epley & Schroeder, 2014; Schroeder et al, 2021) and outgroup members (Mallett et al, 2008; Shelton & Richeson, 2005) because they perceive distant others to be less interested in talking than they are. In the midst of conversation, people are reluctant to reveal negative information about themselves (Kardas et al, 2021a), to seek advice from others (Brooks et al, 2015), and to deliver open and honest feedback (Levine & Cohen, 2018) in part because they expect others to judge them more harshly than others would upon hearing these statements.…”
Section: Discussionmentioning
confidence: 99%
“…Our corpus offers the opportunity to examine this idea at the earliest stages of relationship development-people meeting for the first time-in well-preserved records and at a scale that was hard to achieve before the ubiquity of video chat (and inexpensive online data storage). Our corpus allowed us to not only determine how conversations with strangers increase well-being, but also probe a set of puzzling recent findings about how people consistently underestimate how -35-RUNNING HEAD: CANDOR CORPUS much new conversation partners like them and enjoy their company (e.g., Boothby et al, 2018;Cooney et al, 2021;Epley & Schroeder, 2014;Schroeder et al, 2021;Wolf et al, 2021). Finally, we exploit the breadth of our diverse sample to show how these effects vary across the lifespan.…”
Section: The Primary Social Functions Of Conversation (High-level)mentioning
confidence: 99%